Aberrant epigenetic regulators control expansion of human CD34+ hematopoietic stem/progenitor cells - Faridi, Farnaz; Ponnusamy, Kanagaraju; Quagliano-Lo Coco, Isabell; Chen-Wichmann, Linping; Grez, Manuel; Henschler, Reinhard; Wichmann, Christian (Frontiers in Genetics, 2013)
Transcription is a tightly regulated process ensuring the proper expression of numerous genes regulating all aspects of cellular behavior. Transcription factors regulate multiple genes including other transcription factors that together control a highly complex gene network. The transcriptional machinery can be ‘hijacked’ by oncogenic transcription factors, thereby leading to malignant cell transformation. Oncogenic transcription factors manipulate a variety of epigenetic control mechanisms to fulfill gene regulatory and cell transforming functions. These factors assemble epigenetic regulators at target gene promoter sequences, thereby disturbing physiological gene expression patterns. Retroviral vector technology and the availability of ‘healthy’ human hematopoietic CD34+ progenitor cells enable the generation of pre-leukemic cell models for the analysis of aberrant human hematopoietic progenitor cell expansion mediated by leukemogenic transcription factors. This review summarizes recent findings regarding the mechanism by which leukemogenic gene products control human hematopoietic CD34+ progenitor cell expansion by disrupting the normal epigenetic program.